THE BIOTECHNOLOGICAL POTENTIAL OF THE NEW CROP, Miscanthus cv . SORANOVSKII - N. M. Slynko; T. N. Goryachkovskaya; S. V. Shekhovtsov; S. V. Bannikova; N. V. Burmakina; K. V. Starostin; A. S. Rozanov; N. N. Nechiporenko; S. G. Veprev; V. K. Shumny; N. A. Kolchanov; S. E. Peltek (Вавиловский журнал генетики и селекции, 2015)
Miscanthus cv. Soranovskii was registered as a state breeding achievement in 2013. On the base of phenotyping and DNA sequencing, the new crop was identified as Miscanthus sacchariflorus. The development of methods for converting its biomass to sugar-containing substrate for biotechnological use is in progress. Effects of mechanical and chemical treatments combined with enzymatic hydrolysis on sugar production from Miscanthus biomass have been studied. The best procedure includes grinding to ~100 μm particles followed by treatment with calcium hydroxide. Enzymatic hydrolysis of such materials yields substrates containing 10 to 15 g/L reducing sugars.